A low-cost harmonic radar for tracking very small tagged amphibians - Aumann, Herbert; Kus, Evan; Cline, Brittany; Emanetoglu, Nuri W. (2013 IEEE International Instrumentation and Measurement Technology Conference (I2MTC), 2013)
A low-cost, hand-held harmonic radar is described for tracking tagged amphibians weighting less than a gram during a cryptic period of their life history. The radar is based on inexpensive, commercial 5.8 GHz wireless communications and 11.6 GHz satellite television technology. The performance of the system was accurately predicted from laboratory measurements by defining an appropriate harmonic tag conversion efficiency. The harmonic radar has a demonstrated maximum tag detection range of 20 ft. The best performance was achieved with an asymmetric, dielectric sleeved dipole with a 1:2 arm length ratio.